PRODUCTIVITE TOTALE DES FACTEURS ET MODELES DE MESURE : choix judicieux de méthode d’analyse - MOBONDA, Ricky MOLOKO; AMUNDE , Francis ANYOLE; Y’ANGANDUA , Jules Karl MBAY (IJRDO - Journal of Business Management, 2021)
The difference with new economic growth theories hypothesis and the Solow theory of growth have provided a new methodology framework. This framework established the sustainable choice of parametric measure and non-parametric measure of total productivity of factors(TPF). Those choices which are depended to initial Solow hypothesis allow to release non-parametric analysis to parametric one. Especially, while time series datas or panel datas are used to set econometric method. For this relevant analysis, the GMM lag use TFP like endogenous variable.